Finacial Feasibility and Farmers' Response to Citronella Grass Farming and Processing in Simawang Village, Tanah Datar District - Yusmarni, Yusmarni; Putri, Afrianingsih (International Journal of Agricultural Sciences, 2023)
Simawang village has been experiencing a drought since the 2000s due to the uncertainty of the seasonal pattern. All paddy fields in the village depend on rain for irrigation. Consequently, the activities of paddy farming were also disrupted. Some farmers leave their rice fields unplanted, and there is approximately 60 ha of rice fields in Simawang village have turned into abandoned land. In 2014 the farmers started to plant citronella grass on that abandoned land, and in 2017 they already had a citronella oil distiller. This paper discusses the financial feasibility of citronella grass farming and processing and analyzes the farmers' response to those activities. The research found that citronella grass farming and processing in Simawangv illage is feasible to be implemented. It can be seen from the NPV, IRR, and B/C ratio values of Rp. 218.438.869, 33,2% and 2,1 respectively. Moreover, the farming and processing payback period is two years and 11 months. The cognitive and affective responses of the farmers to farming and processing are good; meanwhile, the conative response is poor. Despite the farmers having good knowledge about farming and processing citronella grass and agreeing that those activities could benefit them both economically and environmentally, most of them have not yet practiced the activities due to land ownership issues.